Evaluation of Fertility Rate in the Couples after Uterine Septum Resection - Vahdat, Mansoureh; Rokhgireh, Samaneh; Afshari, Elahe; Mohammadpour, Samaneh; Hosseini, Mohammad Ali (Archives of Men’s Health, 2019)
Introduction: Uterine septum is one of the most common congenital abnormalities in women that leads to numerous gynecological problems and adverse obstetrics outcomes. This study aimed to evaluate the effects of Hysteroscopic Resection on pregnancy outcomes in women undergone the surgery. Methods: In this quasi-experimental study, 90 women were included from April 2016 to June 2018 from patients attending to Rasoul Akram hospital of Tehran. The inclusion criteria included: the age lower than 35 years old, primary infertility, idiopathic recurrent spontaneous abortion, BMI between 19 and 30, and having informed consen. Septum was resected by scissor upward and lateral. After 10 months of follow-up in average, we assessed rate of live births, abortions, birth weight and presentation. Results: 82 individuals were assessed for occurrence of conception (response rate=91%). The mean age of patients was 30.01 ± 6.76 years and the mean BMI was 26.25 ± 4.88. Out of 82 patients, 36 patients were pregnant, of whom 16 (44.4%) had abortions. 5 (14.9%) of the pregnancies ended with preterm birth, and 6 (17%) ended with stillbirth. Conclusion: The present study showed that the infertile patients with uterine septum and with no other causes of infertility were more likely to be pregnant compared to other patients with idiopathic infertility. Our study showed that post-operation fertility following Hysteroscopic Resection was lower than that in previous reports. According to the findings of this study, scissors may be safe, effective and cost-effective method for removing uterine septa.